Radiation Monitoring Results from the First Year of Operation of a Unique Ambulance-based Computed Tomography Unit for the Improved Diagnosis and Treatment of Stroke Patients. Issue 5 (May 2016) - Gutiérrez, Janet M.; Emery, Robert J.; Parker, Stephanie A.; Jackson, Kamilah; Grotta, James C.
Abstract : Abstract: When a blood clot blocks the blood supply to the brain or when a blood vessel bursts, resulting in brain cell death, the medical condition is referred to as a "stroke." Stroke is a main cause of death worldwide and is a common cause of disability. A common form of stroke, called ischemic stroke, is when blood flow to the brain is decreased. Clinical research has revealed that treatment within the very first hours of symptom onset is key for ischemic stroke with recanalization of occluded arteries by thrombolysis with alteplase. Computed tomography (CT) is one of the diagnostic tools used to determine if this treatment path is appropriate. To determine if health outcomes of possible stroke patients can be improved by decreasing the time from symptom presentation to treatment, the first mobile stroke ambulance unit in the United States was deployed by The University of Texas Health Science Center at Houston (UTHealth) in 2014, equipped with a computed tomography imaging system. The mobile stroke unit shortens the time to treatment for stroke patients by allowing pre-hospital treatment. Having completed its first year of operation, radiation-monitoring data describing the doses delivered to various entities have been characterized. The CT operator's cumulative deep dose equivalent for 1 y of operation was 1.14 mSv resulting from the care of 106 patients. Area monitors were deployed and measurements performed demonstrating that general public doses did not exceed 0.02 mSv h −1 or 1.0 mSv year.